Variation in beliefs about 'fracking' between the UK and US - Evensen, Derrick; Stedman, Richard C.; O'Hara, Sarah; Humphrey, Mathew; Andersson-Hudson, Jessica (IOP Publishing, 2017)
In decision-making on the politically-contentious issue of unconventional gas development, the UK Government and European Commission are attempting to learn from the US experience. Although economic, environmental, and health impacts and regulatory contexts have been compared cross-nationally, public perceptions and their antecedents have not. We conducted similar online panel surveys of national samples of UK and US residents simultaneously in September 2014 to compare public perceptions and beliefs affecting such perceptions. The US sample was more likely to associate positive impacts with development (i.e., production of clean energy, cheap energy, and advancing national energy security). The UK sample was more likely to associate negative impacts (i.e., water contamination, higher carbon emissions, and earthquakes). Multivariate analyses reveal divergence cross-nationally in the relationship between beliefs about impacts and support/opposition – especially for beliefs about energy security. People who associated shale gas development with increased energy security in the UK were over three times more likely to support development than people in the US with this same belief. We conclude with implications for policy and communication, discussing communication approaches that could be successful cross-nationally and policy foci to which the UK might need to afford more attention in its continually evolving regulatory environment.